Factors affecting purchase decision among millennias towards smartphone in Shah Alam / Muhammad Hairi Hizwan Mohd Terudin - Mohd Terudin, Muhammad Hairi Hizwan (Faculty of Business and Management, 2019)
This research objective is to examine the relationship between three hypothesis which is the relationship between brand concern, social influence and product features with millennials purchase decision towards smartphone in Shah Alam. For this purpose of study, the descriptive research was conducted. Convenience sampling has been utilised with 380 respondents as the sample size which 328 questionnaires were answered and collected from the respondents based on their consent and voluntary basis. The result indicates that all of the hypothesis shows a positive relationship and significant between independent variables (brand concern, social influence, and product features) with the dependent variables (Millennials purchase decision). All results and analysis has been evaluated by using SPSS (Statistical Package for Social Science during research been conducted.